Fate of polycyclic aromatic hydrocarbons in the Pacific sector of the Arctic Ocean based on a level III fugacity environmental multimedia model. (May 2021) - Na, Guangshui; Ye, Jiandong; Li, Ruijing; Gao, Hui; Jin, Shuaichen; Gao, Yunze; Hou, Chao; Huang, Jiajin
Abstract: The sink-source controversy for global polycyclic aromatic hydrocarbons (PAHs) in high-latitude seas is extremely concerning. A level III fugacity model was developed for the southern Chukchi Sea to estimate the fate of 16 priority PAHs. The model results indicate large losses were due to seawater advection outflow, followed by degradation in seawater. The Chukchi Sea serves as a source of 4 PAHs (i.e., Nap, Ace, Acp and Fl) in the atmosphere and sediment but acts as a final sink for the other 12 PAHs. The water-air diffusion flux and wet deposition flux play dominant roles in the total transfer flux of the 4 PAHs and the other 12 PAHs, respectively. The source/sink role that high-latitude seas play in PAH distribution has changed under the influence of global climate change. The model proposed in this study provides an approach to support further study of the fate of PAHs in high-latitude seas. Highlights: The fate of PAHs in southern Chukchi Sea is investigated by Level III fugacity model. Air-water exchange of most PAHs is dominant in total cross-interface transfers. Cross-interface transfers is mainly affected by seawater advection and temperature. A sink-to-source reversal of four light molecular weight PAHs has been observed.